Substance-Induced Psychoses: An Updated Literature Review - Fiorentini, Alessio; Cantù, Filippo; Crisanti, Camilla; Cereda, Guido; Oldani, Lucio; Brambilla, Paolo (Frontiers in Psychiatry, 2021)
Background: On the current psychopharmacological panorama, the variety of substances able to provoke an episode of acute psychosis is rapidly increasing. Such psychotic episodes are classified according to the major category of symptoms: positive, negative or cognitive psychotic episodes. On one hand, the abuse of metamphetamines, cannabis and cocaine play a big role in increasing the incidence of episodes resembling a psychotic disorder. On the other hand, the progresses in terms of pharmacodynamic knowledge have led to the synthesis of new drugs, such as cannabinoids and cathinones, which have rapidly entered into the common pool of abusers’ habits. Regarding these newly synthesised substances of abuse, further clinical studies are needed to understand their psychogenic properties. The topic of this review is complicated by the frequent abuse of psychotomimetic drugs by patients affected by psychotic disorders, fact that makes extremely difficult to distinguish between an induced psychosis and a re-exacerbation of a previously diagnosed disorder. Methods: The present narrative review summarizes results from clinical studies, investigating the psychotogenic properties of abuse substances and the psychotic symptoms they can give rise to. It also discusses the association between substance abuse and psychosis, especially with regards to the differential diagnosis between a primary versus a substance-induced psychotic disorder. Findings: Our findings support the theory that psychosis due to substance abuse is commonly observed in clinical practice. The propensity to develop psychosis seems to be a function of the severity of use and addiction. Of note, from a phenomenological point of view, it is possible to identify some elements that may help clinicians involved in differential diagnoses between primary and substance-induced psychoses. There remains a striking paucity of information on the outcomes, treatments, and best practices of substance-induced psychotic episodes.